Fungsi-Fungsi Supervisi Pendidikan - Fehan Alya Rahmi Lubis; Andi Nugraha; Irfan Fauzi (Jurnal Zeniusi, 2025)
Educational supervision plays a very important role in improving the quality of education through various methods or functions, including research, assessment, improvement, and development. The purpose of this article is to thoroughly examine the functions of educational supervision with the aim of improving the quality of teachers' performance. In addition, this research method also employs a literature review by analyzing various reliable sources such as books, scientific journals, and other articles related to the functions of educational supervision. The research results show that educational supervision is not only a control mechanism but also a means of professional development for teachers to enhance their continuous education. The research function helps identify problems and potential in the learning process, in addition, the assessment function provides constructive feedback, the improvement function strives to enhance the quality of student learning, and the coaching function helps teachers develop their potential both academically and in their talents. Effective educational supervision requires collaboration, participation, and an empowering approach aimed at creating a quality educational environment.